PROGRAMAS DE INOVAÇÃO ABERTA NA ÁREA DE QUÍMICA: O CASO DO MINING LAB BEGINNINGS-NEXA QUE CONECTA UNIVERSIDADE-EMPRESA ESTIMULANDO O LICENCIAMENTO DE TECNOLOGIAS E CRIAÇÃO DE STARTUPS - Saulo Luiz Sales Parreiras de Rezende; Rafaela Leal Pereira; Yasmim Rodrigues dos Santos; Eduarda Rezende Barbosa; Rochel Montero Lago; Fabiano Gomes Ferreira de Paula (Química Nova)
In this paper, we present the study-case of the open innovation program Mining Lab Beginnings (MLB), from Nexa Resources, to connect university-industry. The MLB program proposes technological challenges and searches for technologies in very early-stage (“ideas”, technology readiness level (TRL) 1-2) from academic researchers. After mapping and selecting early-stage technologies throughout Brazilian Universities, Nexa finances a collaborative development of the ideas which significantly increases the chances of success. In the MLB, the initial challenge was the “Development of viable products from the jarosite waste” with 37 solutions mapped from universities, of which 6 were tested in the lab to reach TRL 3-4 (Phase 1) to prove the technical and preliminary economic feasibility. The academic teams received technical support and weekly mentoring throughout this phase. From this Phase 1 - Lab, 3 technologies were selected for the “Go-to-Market” (Phase 2) to reach TRL 6-7, focused on product development in relevant environment. After these phases, Nexa started the implementation of 2 technologies in an operational plant for the conversion of jarosite into two products. Moreover, one of the technologies is currently being transferred to another company. The MLB exemplifies how open innovation strengthens cooperation between universities-industry and promotes innovation.